Metal ion-manipulated afterglow on rhodamine 6G derivative-doped room-temperature phosphorescent PVA films - Maida, Margarita Claudya; Sugawara, Natsumi; Suzuki, Airi; Ito, Masato; Kubo, Yuji (Frontiers in Chemistry, 2024)
The long-lived room-temperature phosphorescence (RTP) originating from thiophene boronate polyvinyl alcohol (PVA) has enabled the creation of metal-ion-responsive RTP films doped with spirolactam ring-containing rhodamine 6G (1). In this study, RTP-active PVA films, namely, TDB@PVA and ATB@PVA, were prepared through boronate esterification of thiophene-2,5-diboronic acid (TDB) and 5-acetylthiophene-2-boronic acid (ATB) with the diol units of PVA. The delayed emission properties were evaluated, revealing an emission band at 477 nm with a turquoise afterglow for TDB@PVA and at 510 nm with a green afterglow for ATB@PVA after UV light irradiation ceased. The photophysical properties were assessed using TD-DFT and DFT calculations at the B3LYP/cc-pVDZ level. N-(rhodamine-6G)lactam dye with a salicylimine unit (1) was doped into the RTP-based PVA films, producing a multicolored afterglow upon the addition of metal ions. This phenomenon is explained by a triplet-to-singlet Förster-type resonance energy transfer process from the cross-linked thiophene boronate in PVA to the metal-ion-activated colored form of 1. This photophysical feature finds applicability in encryption techniques. Notably, the reversible metal-ligand coordination of 1 in the PVA system enabled a write/erase information process.